FORMATION OF THE NURSES’ PROFESSIONAL ATTITUDES FOR WORK IN EMERGENCY SITUATIONS - Jankovska, Livija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
While the transformation of the medical education in general is competence-oriented and practice based, the article focuses on the role of the attitudes for the development of the nurses’ education and profession. Covid-19 critical conditions created new complicated cognitive, professional and psycho-emotional challenges for health care specialists. Nurses’ work ability and professional attitudes have become the central factor to solve clinical and personal problems in order to provide patient-centered and effective medical care. However, it shows that   nurses do not have all the necessary competences to quickly adapt, react and keep psycho-emotional balance, working in critical situations. Theoretical analyses and empirical investigations are aimed at finding out what skills and attitudes are essential for medical specialists in Covid-19 pandemic conditions and how students feel about their readiness to use necessary skills and attitudes in practice in unexpected and complicated conditions The article discusses how to transform the organisation of the medical college study process and content to give students opportunities to acquire experience and develop necessary attitudes for the complicated practice. The focus is on studying the nurses’ attitudes necessary for the Covid 19 situation and possibility to promote them in the authentic work-based study process. The study of theoretical sources and survey results give evidence that practice-based studies can promote medical students’ professional attitudes and psycho-emotional capacity, if medical studies are aimed at forming emergency oriented skills and structured in the practice-based environment.  Implementation of attitudes as outcome into programmes and effective transition of attitudes into practice can promote higher quality of nurses’ professional and responsibility level.